“Mind” as Humanizing the Brain: Toward a Neurotheology of Meaning - Ashbrook, James B. (Zygon, 1997)
The concept “mind” refers to the human and humanlike features of the brain. A historical review of thinking about the mind contextualizes humanity's search to understand itself by sketching biblical and philosophical perspectives from the Hebrew scriptures through the Greeks and Descartes to the German philosophers Goethe, Kant, and Hegel. These provide an enlarged context for an analytic approach to mind as focusing on the interface between physical signals and experiential symbolic expressions. Drawing on a holistic paradigm, several features are discernible: empathic rationality, imaginative intentionality, meaningful memory, and adaptability. These reflect the evolutionary development of uncommitted cortex that contributes to the brain's explosive capacity for order, complexity, and novelty. The basic issue continues, namely, how are the distributed modules of information-processing integrated into the meaning-making reality of human beings?